Mathematical modeling and computational outcomes for the thermal oblique stagnation point investigation for non-uniform heat source and nonlinear chemical reactive flow of Maxwell nanofluid. (January 2023) - Chu, Yu-Ming; Abbasi, Aamar; Al-Khaled, Kamel; Farooq, Waseh; Khan, Sami Ullah; Khan, M. Ijaz; Eldin, Sayed M.; Guedri, Kamel
Abstract: Owing to fine thermal prospective of nanomaterials, different applications have been addressed in nanotechnology and thermal management systems. Multidisciplinary applications of such nanomaterials are commonly observed in nuclear reactors, thermal systems, transportation systems, industrial products cooling, power industry, renewable energy etc. The motivated work aims to predicts improved thermal consequences of Maxwell nanofluid with applications of non-uniform heat source and radiated phenomenon. The heat transfer analysis is assessed by using the Cattaneo-Christov theories. The thermal phenomenon is controlled with interference of slip effects. The flow pattern is based on the oblique stagnation point flow confined by stretched cylinder. The Keller Box numerical determination of problem is worked out with fine accuracy. The physical dynamic of flow parameters is visualized graphically. It is claimed that control of thermal transportation phenomenon is resulted when the slip effects are dominant. The exponential heat source with nonlinear radiated phenomenon is important when enhancement in thermal process needed.